Preaching What We Practice: Theories-in-Use in Community Development - Bernie Moore; Lillian H. Hill (Adult Education Research Conference, 1998)
This paper examines theories-in-use among community development practitioners and attempts to bridge the schism between practice and theory by articulating implicit theories utilized in practice.